Penatalaksanaan Fisioterapi Pada Kasus Asma Bronchiale Di Balai Pengobatan Penyakit Paru-Paru (BP4) Yogyakarta - Ustadzi, Imam, Isnaini Herawati, SST., FT,Msc (2015)
Backgroud: asthma is a common respiratory disease that is characterized by multiple symptoms of shortness of breath, followed by a wheezing sound. the problem of physiotherapy in astmha are shortness of breath, wheezing, cough and sputum expenditure (Putri and soemarmo, 2012). Objective: to know the management of physiotherapy to reduce shortness of breath, a sputum sample, increasing the peak expiratory flow and normalize breathing patterns with modalities nebulizer and diafragmatic breathing exercise. Methods: A case study by administering nebulizer and diafragmatic breathing exercise after 6 times obtained results. Results: after the therapy 6 times showed a reducation in breathlessness T1: 8cm into T6: 4cm, auscultation sputum T1: weezing and ronchi loud sounds become T6: weezing sound and ronchi slowly, improved peak expiratory flow T1: 120 liters/min became T6: 280 liters/min, breathing patterns T1: pursed lips breathing becomes T6: do not use the pursed lips already breatjing when breathing. Conclusion: nebulizer and diafragmatic breathing exercise can reduce breathlessness, sputum helps expenses, increase peak expiratory flow and noemalize breathing patterns.